Design, synthesis, in vitro and in silico studies of novel Schiff base derivatives of 2‐hydroxy‐4‐methoxybenzamide as tyrosinase inhibitors. Issue 4 (19th December 2020) - Iraji, Aida; Panahi, Zahra; Edraki, Najmeh; Khoshneviszadeh, Mahsima; Khoshneviszadeh, Mehdi
Abstract: Due to the fact that tyrosinase is responsible for biosynthesis and regulation of melanins and browning food products, tyrosinase inhibitors can be favorable agents in cosmetics and medicinal industries. A series of novel 2‐hydroxy‐4‐methoxybenzohydrazide were designed, synthesized, and their new application as tyrosinase inhibitors was also disclosed. Based on in vitro tyrosinase inhibitory assay, 4d as the strongest inhibitor of tyrosinase with an IC50 value of 7.57 μM showed approximately 2.5‐fold better inhibition than kojic acid as positive control followed by two compounds 4b (IC50  = 8.19 ± 0.25 μM) and 4j (IC50  = 8.92 ± 0.016) which displayed preferable tyrosinase inhibitory activity. Detailed investigations on the mechanism of action of the 4d reported mix type of inhibition. More importantly, molecular modeling assessments proposed the ability of 4d for potential interaction with Cu (metal)‐His (residue) within tyrosinase active site. Overall, 4d is a promising candidate for the development of anti‐tyrosinase agents. Abstract :